PENGARUH PEMANFAATAN TEKNOLOGI INFORMASI DAN KOMITMEN ORGANISASI TERHADAP KINERJA PEGAWAI PADA MASA PANDEMI COVID19 DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA BANJARMASIN - Muhammad Rizalni; Khuzaini; Apriya Santi (Jurnal Ilmiah Ekonomi Bisnis, 2022)
Abstract:The purpose of this research is to determine the effect of the utilization of information technology on employee performance and the effect of organizational commitment on employee performance partially and simultaneously at The Department of Population and Civil Registration of Banjarmasin City with 64 respondents. By using the Multiple Linear Regression test, the results of research show that the utilization of information technology on employee performance has a significant value < 0.05, so it can be concluded that the variable of utilization of information technology partially has a significant effect on employee performance. Likewise the variable organizational commitment partially has a significant effect on employee performance, the variable of information technology utilization and organizational commitment simultaneously have a significant effect on employee performance at the Department of Population and Civil Registration of Banjarmasin City. Keywords: Utilization of Information Technology, Organizational Commitment, Performance